Factors driving FIFA world cup 2022 viewership ratings in mainland China: marketing outlooks for FIFA world cup 2026 - Wang, Zongqing; Su, Lide; Agudamu,; Gong, Tao; Bu, Te; Zhang, Yang (Frontiers in Sports and Active Living, 2024)
Introduction The FIFA World Cup is not only the most lucrative athletic event globally, but it also functions as a platform for promoting peace owing to FIFA's new vision. Nevertheless, the determinants of TV viewership ratings, especially in the Chinese market, which is a critical revenue stream for FIFA TV broadcasting, are still unsolved. Using a distributional regression, this study aimed to quantify the dynamics of viewership ratings for the FIFA World Cup 2022 in mainland China. Methods The CCTV viewership ratings were modeled using 12 covariables related to Chinese TV consumer behavior. Given the data structure, a Logit Normal regression model was chosen to fit the location and dispersion parameters of viewership ratings to explanatory variables. Results In the fitted heteroscedastic model, the viewership ratings dynamics in mainland China were driven by the match kick-off time: μ^=logistic[−4.874+0.043×matchkick-offtime]. In addition, the model captures the factors that influence the variations in viewership ratings: σ^=exp[−14.26–1.346 (if, FIFA World Cup champion = “Yes”) + 0.004 × FIFA world ranking]. Thus, it shows that the FIFA World Cup champions tamp down such variations, leading to a more stable viewing behavior among Chinese consumers. Conclusions Time- and team-sensitive strategies are proposed to aid in crafting uncertainty-suppressing business decisions for the FIFA World Cup 2026. Ultimately, in the more insecure 2020s, a broader live coverage of the FIFA World Cup would be invaluable for promoting peace.